2021
DOI: 10.1186/s43055-021-00450-z
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance diffusion tensor imaging of acute spinal cord injury in spinal trauma

Abstract: Background It was important to develop a non-invasive imaging technique for early evaluation of spinal cord integrity after injury; MRI was the method of choice for evaluation of any cord abnormalities. However, some patients have symptoms with no detectable abnormalities by MRI. The purpose of our study was to assess the role of diffusion tensor MRI in evaluating the integrity of spinal cord fibers in case of spinal trauma. Results Out of the stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…However, at least another study using intrathecal administration of autologous adMSCs showed no interval change in lesion site between baseline and at the 8-month follow-up MRI, post-treatment ( 13 ). Moreover, while MRI has become a conventional imaging technique for spinal cord injuries, it has been suggested that its usage may be limited because of the non-specificity of changes in signal intensity that do not directly reflect physiological changes ( 29 ). Additionally, there is evidence that MRIs are more effective when used acutely following a spinal cord injury, specifically within the first 72 h, for prognostication, as opposed to being used for management over lengthy durations of time, as was done in this study ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, at least another study using intrathecal administration of autologous adMSCs showed no interval change in lesion site between baseline and at the 8-month follow-up MRI, post-treatment ( 13 ). Moreover, while MRI has become a conventional imaging technique for spinal cord injuries, it has been suggested that its usage may be limited because of the non-specificity of changes in signal intensity that do not directly reflect physiological changes ( 29 ). Additionally, there is evidence that MRIs are more effective when used acutely following a spinal cord injury, specifically within the first 72 h, for prognostication, as opposed to being used for management over lengthy durations of time, as was done in this study ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…28 Another application of DTI is diffusion tensor tractography, which enables three-dimensional demonstration of the white matter fibers (axons). 1…”
Section: Applicationsmentioning
confidence: 99%